2017
DOI: 10.1177/0960327117698542
|View full text |Cite
|
Sign up to set email alerts
|

Designer drugs: Review and implications for emergency management

Abstract: In the past 10 years, "designer drugs" such as synthetic cannabinoids and cathinones have emerged and come into widespread use, resulting in more overdose cases involving these new drugs in the United States. Emergency departments regularly treat a diverse array of drug intoxications, and providers must be cognizant of novel drugs of abuse and the associated clinical presentations in order to provide the most appropriate care. This review aims to describe the epidemiology, mechanism of action, clinical present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Behavioral factors such as physical exercise [68] and healthy dietary lifestyle measures via an increased anti-oxidative capacity have been shown to be a promising approach in the management of psychostimulant addiction [69]. There is currently no remedy for SC intoxication, except for supportive care [70]; however, the oxidative stress mechanistic pathway suggests the possibility of efficacious antioxidant pharmacotherapies for attenuating SC-induced ROS production [71]. Considering that mitochondrial dysfunction plays a critical part in SC-induced neurotoxicity, the enhancement of mitochondrial function [72] and mitochondrial transplantation [73] have received attention as strategies that might ameliorate the associated mitochondrial neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral factors such as physical exercise [68] and healthy dietary lifestyle measures via an increased anti-oxidative capacity have been shown to be a promising approach in the management of psychostimulant addiction [69]. There is currently no remedy for SC intoxication, except for supportive care [70]; however, the oxidative stress mechanistic pathway suggests the possibility of efficacious antioxidant pharmacotherapies for attenuating SC-induced ROS production [71]. Considering that mitochondrial dysfunction plays a critical part in SC-induced neurotoxicity, the enhancement of mitochondrial function [72] and mitochondrial transplantation [73] have received attention as strategies that might ameliorate the associated mitochondrial neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that awareness and confidence of clinicians can be significantly influenced by targeted training/education. [43] ED physicians should be trained in recognizing the presentation features of the intoxications caused by the main illicit substances and support the vital functions [20,23,25], the indications to the available antidotes [18,19,47], and the prevention of severe withdrawal symptoms [34].…”
Section: Discussionmentioning
confidence: 99%
“…Popular designer drugs include synthetic cannabinoids (K2, Spice), synthetic cathinones (bath salts), nontraditional opioids (kratom, salvia, Krokodil), opioid analogs (U-47700), and dissociative agents (PCP, ketamine, dextromethorphan) [20].…”
Section: Synthetic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, most drug abuse and addiction cases involved amphetamines, cannabis, cocaine and heroin, whereas nowadays NPS are an increasing problem. The European Monitoring Centre for Drugs and Drug Addiction notes that > 450 NPS have been introduced for illegal use since 2004 [28,29].…”
Section: Discussionmentioning
confidence: 99%